Change Management At PT Industri Nabati Lestari: Reduced Working Hours During the Covid-19 Pandemic - Anggraini, Yulia (LPPJPHKI Universitas Dehasen Bengkulu, 2024)
This journal discusses the implementation of change management at PT Industri Nabati Lestari during the COVID-19 pandemic period, with a focus on reducing working hours. The COVID-19 pandemic has caused significant disruption in various industrial sectors, including the food and beverage industry. PT Industri Nabati Lestari faced similar challenges and adopted changes in employee work schedules in response to the difficult situation. This journal describes the strategies used, the impact of those changes, as well as the change management measures taken by PT Industri Nabati Lestari. this research be useful? Name the area, discipline, and so on.